The Great Telecom Meltdown - Goldstein, Fred (Artech House telecommunications library, 2005)
In today's telecom business environment, a thorough and accurate understanding of past mistakes goes a long way in ensuring future success. Providing you with an authoritative account of what contributed to the Great Telecom Crashù, this insightful resource explores the roots of the perfect storm that buffeted telecom and Internet companies and investors. You get a detailed insider's look at how the crash was caused by a complex combination of risk and regulatory factors in an increasingly competitive environment, originally fueled by the break up of AT&T. The Great Telecom Meltdown offers you a solid understanding of the evolving structure of the information, communications and telecom industries, and how companies and sectors within these industries relate to each other. You gain insight into identifying sound long-term investment strategies and avoiding fads with unsound fundamentals. The book helps you make sense of the regulatory framework that has been evolving, as competition gradually replaces regulation among different industry sectors. Moreover, you gain an appreciation for the context of the modern telecom industry, leading up to and beyond the Telecom Act of 1996, which, as the book explains, has been given more credit and more blame for the events of the era than it deserves.